2019
DOI: 10.1136/jim-2018-000750
|View full text |Cite
|
Sign up to set email alerts
|

Associations of hormonal contraceptives and infertility medications on the risk of venous thromboembolism, ischemic stroke, and cardiovascular disease in women

Abstract: The purpose of this study was to examine the relations of hormonal contraceptives and infertility drugs with the risk of venous thromboembolism (VTE), deep vein thrombosis (DVT), pulmonary embolism (PE), ischemic stroke, and cardiovascular disease. The Taiwan National Health Institute Research Database was searched for women who had taken hormonal contraceptives or infertility medications from 2000 to 2010. The two groups were age and index date matched with controls (1:4 ratios). Cox regression analysis was u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(32 citation statements)
references
References 25 publications
0
30
2
Order By: Relevance
“…Among females, VTE risk is elevated among those using estrogen-based contraceptives, hormone therapy, or infertility treatment. 35…”
Section: Venous Thromboembolism (Deep Vein Thrombosis and Pulmonary E...mentioning
confidence: 99%
“…Among females, VTE risk is elevated among those using estrogen-based contraceptives, hormone therapy, or infertility treatment. 35…”
Section: Venous Thromboembolism (Deep Vein Thrombosis and Pulmonary E...mentioning
confidence: 99%
“…Among females, VTE risk is elevated among those using estrogen-based contraceptives, hormone therapy, or infertility treatment. 40…”
Section: Venous Thromboembolism (Deep Vein Thrombosis and Pulmonary E...mentioning
confidence: 99%
“… 44 Differences in findings may be influenced by variability in exposure definitions (eg, experiencing infertility versus using treatment for infertility, which is also influenced by access to care), outcome definitions (ischemic versus hemorrhagic stroke, fatal versus nonfatal stroke), and differences in the demographics of the population sampled. Indeed, focusing on ischemic stroke only, prior research among women enrolled in the Taiwan National Health Insurance program observed a protective effect for women using infertility treatment (HR, 0.82) 45 ; however, a harmful effect was observed for women with a history of infertility in the InterLACE pooling project (HR, 1.15). 43 …”
Section: Discussionmentioning
confidence: 99%